State of the art de novo assembly of human genomes from massively parallel sequencing data - Li Yingrui; Hu Yujie; Bolund Lars; Wang Jun (Human Genomics, 2010)
Abstract Recent studies in human genomes have demonstrated the use of de novo assemblies to identify genetic variations that are difficult for mapping-based approaches. Construction of multiple human genome assemblies is enabled by massively parallel sequencing, but a conventional bioinformatics solution is costly and slow, creating bottle-necks in the process. This review describes two public short-read de novo assembly applications that can handle human genomes, ABySS and SOAPdenovo. It also discusses the technical aspects and future challenges of human genome de novo assembly by short reads.